Asuhan Keperawatan pada Lansia TN. D dengan Diagnosa Medis Gout Arthritis - Muhammad Luthfi; Dwin Seprian; Wulida Litaqia; Ainun Najib Febrya Rahman; Haryati Septiani (MES Bogor, 2025)
Gout arthritis is a form of joint inflammation caused by purine metabolism disorders, leading to elevated uric acid levels in the bloodstream (hyperuricemia). The accumulation of monosodium urate crystals in joint tissues due to this condition triggers acute inflammation and severe pain. Elderly individuals are particularly susceptible due to reduced metabolic function and decreased efficiency in uric acid excretion. This study aims to evaluate the nursing care provided to patients with gout arthritis, with a focus on pain management, sleep disturbances, and patient education regarding the disease and its management. This research employs a descriptive case study approach, emphasizing scheduled activity interventions for gout arthritis patients. Data collection was conducted through interviews, physical examinations, and observations, with findings presented in a descriptive case report format. The assessment revealed that the patient experienced severe pain in the metatarsophalangeal joint, with moderate to high pain intensity. Additionally, the patient struggled with sleep disturbances caused by pain and lacked awareness of the appropriate dietary measures for managing uric acid levels. Nursing interventions included pain management strategies, patient education on a low-purine diet, and supportive measures to enhance sleep quality. Effective nursing interventions for gout arthritis patients can significantly improve their quality of life by alleviating pain, enhancing sleep patterns, and increasing disease management awareness. Continuous patient education and adherence to therapy are essential in minimizing recurrence risks and preventing future complications.